Field maintenance at rubber plantation by using Global Positioning System (GPS) / Muhammad Azamuddin Radhi - Radhi, Muhammad Azamuddin (Faculty of Plantation and Agrotechnology, 2019)
Rubber industry is the one of major agriculture sector in Malaysia after oil palm and paddy sector. There is 75.6 percent of domestic consumption of natural rubber in the middle of year 2018. The increasing of rubber consumption needs a plantation sector to manage a good method in the field maintenance program. The precision farming is the method of combination technology in the plantation management. The Global Position System (GPS) and Geographical Information System (GIS) were used for collect the data for planning, analyzing and evaluating the field maintenance program. The study was done at the UiTM rubber planting area. The data was collected at the field to determine dead, infection and healthy rubber tree. The data of tree sample was transferred to the Map Source Application to determine the total number of rubber tree at the area. The result showed there are 667 rubber tree divided into 3 types of rubber tree condition which is dead (54 trees), infection (38 trees) and healthy tree (575). As the conclusion the field maintenance program will increase the work of productivity by using the precision farming method in the rubber plantation. The proses of field maintenance program can be planned, monitored and evaluated easily at the management and minimize the period work rather than conventional method.